Enhanced mechanical properties and interfacial interaction of ESBR composites by introducing silica decorated with epoxy functionalized elastomer. (August 2022) - Li, Qiao; Lin, Guangyi; Zhang, Su; Zhang, Lin; Geng, Chuanbao; Borah, Jyotishmoy
Abstract: An epoxy functionalized elastomer (ethylene-vinyl acetate-glycidyl methacrylate terpolymer) (EVMG) was used as macromolecular modifier to prepare SiO2 @EVMG organic hybrid materials modified with SiO2 . The self-polymerization of dopamine on the surface of in-situ generated SiO2 forms a polydopamine (PDA) layer, which provides a reaction platform to prepare organic hybrid materials. During the preparation of SiO2 @EVMG organic hybrid materials, a ring-opening reaction takes place between the amine group and catechol of the PDA and the epoxy groups of EVMG via covalent bonding interfaces between SiO2 -PDA and EVMG. ESBR/SiO2 @EVMG composites were prepared without silane coupling agent. The incorporation of grafted epoxy functionalized elastomer EVMG on the surface of SiO2 resulted an improvement of the dispersion of SiO2 and the interfacial interaction between SiO2 and ESBR, which were analyzed and verified in detail by dynamic mechanical analysis (DMA) and rubber process analyzer (RPA). It has been observed that the tensile strength, wear resistance and the wet skid resistance are increased by 63.1%, 30% and 26.5%, respectively when compared with ESBR/SiO2 composites, this provides an unique idea for the preparing high performance green tires. Highlights: EVMG was used as macromolecular modifier. A ring-opening reaction between the amine and catechol of the PDA and the epoxy groups. SiO2 @EVMG had steric hindrance effect. Mechanical properties and wet skid resistance of rubber composites increase.